Raw sensor data (CTD, Fluorometer, turbidity, redox potential) and vehicle performance for AUV dive ABYSS 0380 during RV SONNE cruise SO295 - Matthias Haeckel; Pedro Martínez Arbizu; Ulrike Lomnitz; Emanuel Wenzlaff (PANGAEA, 2024)
A total of seventeen missions of the autonomous underwater vehicle (AUV) Abyss was performed from October to December 2022 in the German and Belgian license areas of the Clarion-Clipperton Zone (CCZ) in the Northeast Pacific during RV SONNE cruise SO295. Each dive lasted a few hours and recorded information for a number of sensors including CTD (Seabird SBE49FastCAT), ECO (=combined fluorometer and turbidity senso; Wetlabs FLNTU/0712017), REDOX-sensor (Eh-sensor by Ko-Ichi Nakamura from AIST, South Korea) . The sensor data is recorded in separate files for each dive. The vehicles performance under water and core functions (roll, pitch, heading, power use, and many others) are recorded in the STATE file of each dive.
In: Haeckel, M et al. (2024): AUV ABYSS sensor data (CTD, Fluorometer, turbidity, redox potential) and vehicle performance for dives during RV SONNE cruise SO295 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.971853